Gerakan Salafiyah: Islam, Politik dan Rigiditas Interpretasi Hukum Islam - Salman, Abdul Matin bin (IAIN Samarinda, 2017)
Salafiyah lately has become the scourge of modern states because the banality of their interpretation of Islamic law is considered rigid and not in line with the global world that is increasingly plural. This article attempts to discuss the various variants of salafism and the purpose behind its militant movement. The fundamental question in this article is about the purpose behind a non-compromising understanding of other understandings that are different from the Salafiyah. This article first describes some variant of Salafism, namely: al-Salafiyah al-TÄrÄ«khiyah, al-Salafiyah al-WahÄbiyah, al-Salafiyah al-IshlÄhiyah, al-Salafiyah al-Taâ€™sÄ«liyah dan al-Salafiyah al-JihÄdÄ«yah al-TakfÄ«riyah, and then analyze what the similarity of theological traits of these variant. This study confirms that Salafism is a doctrinal social movement that has political efforts to establish Islam by rejecting the differences that exist. The results of this study indicate that the Salafi initially is group that calls on Muslims to return to the original sources of the Qur'an and the Hadith leads to the resurrection of a new Islamic civilization against the Western world power hegemony (especially the United States), it becomes a group which is face to face with the Muslims themselves. In addition, a rigid interpretation of Islamic law has meaning to build political strength to slowly unify differences that do not correspond with the values of salafiyah.Â Keywords: Variant of Salayifah, siyÄsah islÄmiyah, interpretation of Islamic law.Â